Overview [in Africa agriculture trade monitor 2020] - Bouët, Antoine; Odjo, Sunday P.; Zaki, Chahir (International Food Policy Research Institute, 2020)
The objective of this first chapter is to provide an overview of recent issues related to agricultural trade in Africa. Hence, the next section explains how regional integration has experienced some new trends, yet is still impeded by old and structural issues. The following section provides an analysis of informal trade flows, given their importance for agriculture in Africa. In addition, we look at the unprecedented shock of COVID-19 as it can be expected to have a major impact on trade and food security in Africa. The final section describes some issues concerning data and methodology for this report.